2010
DOI: 10.1186/cc8890
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged mechanical ventilation in a respiratory-care setting: a comparison of outcome between tracheostomized and translaryngeal intubated patients

Abstract: IntroductionMechanical ventilation of patients may be accomplished by either translaryngeal intubation or tracheostomy. Although numerous intensive care unit (ICU) studies have compared various outcomes between the two techniques, no definitive consensus indicates that tracheostomy is superior. Comparable studies have not been performed in a respiratory care center (RCC) setting.MethodsThis was a retrospective observational study of 985 tracheostomy and 227 translaryngeal intubated patients who received treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
21
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 12 publications
(18 reference statements)
8
21
1
Order By: Relevance
“…8,22 Second, the RSBI tends to be higher in PMV patients, probably because these chronically ill patients are more likely to assume a rapid shallow breathing respiratory pattern, due to muscle wasting and weakness, and does not predict weaning outcome in these patients. 23,24 Accordingly, it is not surprising that the present study did not find an association between the RSBI and extubation outcome in the IRCU setting.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…8,22 Second, the RSBI tends to be higher in PMV patients, probably because these chronically ill patients are more likely to assume a rapid shallow breathing respiratory pattern, due to muscle wasting and weakness, and does not predict weaning outcome in these patients. 23,24 Accordingly, it is not surprising that the present study did not find an association between the RSBI and extubation outcome in the IRCU setting.…”
Section: Discussioncontrasting
confidence: 46%
“…Consistent with prior studies, 11,25 we did not demonstrate an association between long-term survival and the APACHE II score. Although such an association has been reported in a few studies, 24,26,27 they primarily investigated mortality over a short period of time, and found that the APACHE II score was poor at discriminating between individual patients in terms of risk of death. 27 Development of a severity scoring system for PMV patients is important because these patients consume a disproportionate amount of healthcare resources and have high medical costs.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These results are comparable with those of other studies reported in Taiwan 12,16 . Because the NHIB established a policy of gradual care reduction for these patients, as demonstrated by their transfer from the ICU after 21 days to an RCC and then to a respiratory care ward (RCW) after 42 days in the RCC, the outcome of patients with PMV became favorable as compared with recent studies 17e19 .…”
Section: Discussionsupporting
confidence: 96%
“…The APACHE II was useful in predicting mortality in pulmonary ICU patients with a cut-off point of 16 points (AUROC = = 0.81) [16]. In a comparison between tracheostomized and translaryngeally intubated patients, those with an APACHE II score < 18 points were more likely to be successfully weaned and be kept alive [17]. Jubran et al confirmed that the comorbidity score might increase mortality by 24% [18].…”
Section: Discussionmentioning
confidence: 99%